Seasonal and spatial variations in the occurrence, mass loadings and removal of compounds of emerging concern in the Slovene aqueous environment and environmental risk assessment. (November 2018) - Česen, Marjeta; Heath, David; Krivec, Marko; Košmrlj, Janez; Kosjek, Tina; Heath, Ester
Abstract: This study reports the development of a multi-residue method for determining 48 compounds of emerging concern (CEC) including three diclofenac transformation products (TP) in Slovenian wastewater (WW) and surface water (SW). For solid-phase extraction (SPE), Oasis™ Prime cartridges were favoured over Oasis HLB™. The validated method was then applied to 43 SW and 52 WW samples collected at nine locations. Ten bisphenols in WW and 14 bisphenols in SW were traced in Europe for the first time. Among all of the 48 targeted CEC, 21 were >LOQ in the influents and 20 in the effluents. One diclofenac TP was also quantified in WWs (3.04–78.1 ng L −1 ) for the first time. As expected, based on mass loads in the wastewater treatment plant influents, caffeine is consumed in high amounts (105, 000 mg day −1 1000 inhab. −1 ) in Slovenia, while active pharmaceutical ingredients (APIs) are consumed in lower amounts compared to other European countries. Removal was lower in winter in the case of four bisphenols (17–78%), one preservative (36%) and four APIs (-14–91%), but remained constant for caffeine, one API, two UV-filters and three preservatives (all >85.5%). Overall, a constructed wetland showed the lowest (0–80%) and most inconsistent removal efficiencies (SD > 40% for some CECs) of CECs including caffeine, two UV-filters, two preservatives and two APIs compared to other treatment technologies. The method was also able to quantify Bisphenol S in SW (<36.2 ng L −1 ). Environmental risk was assessed via risk quotients (RQs) based on WW and SW data. Two UV-filters (oxybenzone and dioxybenzone), estrone and triclosan, despite their low abundance posed a medium to high environmental risk with RQs between 0.282 (for HM-BP) and 15.5 (for E1). Graphical abstract: Image 1 Highlights: First analysis of 48 CEC in SW/WW using Oasis Prime cartridges. Recovery of 8 CEC in SW and 13 CEC in WW was higher (≥40%) with Prime than HLB cartridges. A novel diclofenac transformation product was quantified > LOQ in SW and WW. Bisphenol S was quantified in European SW for the first time. Levels of UV-filters HM-BP and DH-BP, estrogen E1 and triclosan pose a medium/high environmental risk. Abstract : This study describes the analysis of compounds of emerging concern in surface and wastewaters using novel Oasis Prime cartridges, where the results contribute to the body of existing data on their occurrence in the European aqueous environment.